The Influence of the Online Learning System on the Professionalism of Lecturer Performance at University - Samsul Bahri; Disna Anum Siregar; Ulian Barus; Nurjannah Nurjannah; Saiful Bahri (STAI Hubbulwathan Duri, 2023)
This study aims to describe the influence of the online learning system on the professionalism of the performance of lecturers at the university, which has around 300 staff from Kopertis, Foundation, and Extraordinary. As a percentage of educational qualifications, 85% have received a master's degree. The research method used is a qualitative descriptive research method with data collection carried out through literature studies, observation, document analysis, and literature studies. The results of the study show that leadership is still considered the dominant factor influencing the success and failure of an organization. Lecturer professionalism is stated if the lecturer fulfils the lecturer's workload, which includes main activities: planning, process implementation, evaluation of learning outcomes, guidance and training, and conducting research. In addition, carrying out additional duties and community service. The Covid-19 era that hit Indonesia has also changed the perception and implementation regarding the professionalism of the performance of lecturers. The university issued guidelines on preventing Covid-19 by making nine policy steps, namely extending distance lectures until the even semester of the 2019/2020 academic year, providing special treatment for students who experience difficulties in online remote lectures such as network disruptions (among other things can be replaced by learning through modules, assignments to make scientific work and others), guidance activities and implementation of proposal seminars are carried out through online facilities and may meet face to face with due observance of Covid-19 handling standards and the maximum number of attendees is five people namely two supervisors, one examiner as well as students attending green table sessions and the head of the study program.